Empowering Member of PKK Through Assistance in Increasing Productivity of Papaya Chips Business: Pemberdayaan; Pendampingan; Peningkatan Produktivitas; Kualitas Produksi - Taufik, Ahmad; Yoga Vandita, Lalu; Prayunisa, Fena (Majalah Ilmiah UPI YPTK, 2025)
This community service program (PKM) was implemented in Jago Village, Praya District, Central Lombok Regency, which is known as one of the papaya producing areas. This village faces a major problem when the harvest season arrives, especially because many papayas that meet the standards are not export (grade Ab1 or local (grade Ab2), resulting in a pile of fruit that eventually rots and has the potential to pollute the environment. To overcome this problem while improving the village economy, the 2025 PKM DRTPM Kemenristek Grant fund together with the Nusantara Global Education Institute Campus supports the development of Papaya chip products in Jago Village, so that they can be marketed well and provide significant economic benefits. The methods used in this activity include Socialization, Training, and Evaluation. The results of this activity showed a positive response from the participants, but further assistance is needed to ensure more optimal results in the future.